2017
DOI: 10.1364/oe.25.020983
|View full text |Cite
|
Sign up to set email alerts
|

Mask aligner lithography using laser illumination for versatile pattern generation

Abstract: Mask aligner lithography is a well-established back-end fabrication process in microlithography. Within the last few years, resolution enhancement techniques have been transferred and adapted from projection lithography to further develop mask aligner lithography, especially concerning achievable resolution. Nonetheless, current technology using a mercury vapor lamp as a light source has reached its limits, e.g. for high-resolution pattering. Within this paper, we present the extension of the existing mask ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In comparison, excimer laser sources for mask-aligner lithography have been demonstrated with an optical power of 7.5 W at 193 nm [4]. Weichelt et al reported on a pulsed solid-state laser source with an optical power of 3 W and emitting at a wavelength of 355 nm [7]. The laser output exhibits an elliptical beam profile, as depicted in the inset of Fig.…”
Section: Optical Setup and Beam Shapingmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, excimer laser sources for mask-aligner lithography have been demonstrated with an optical power of 7.5 W at 193 nm [4]. Weichelt et al reported on a pulsed solid-state laser source with an optical power of 3 W and emitting at a wavelength of 355 nm [7]. The laser output exhibits an elliptical beam profile, as depicted in the inset of Fig.…”
Section: Optical Setup and Beam Shapingmentioning
confidence: 99%
“…The integration of LED and diode laser light sources into mask-aligner lithography has been demonstrated [6][7][8], solving the task of beam shaping for uniform mask illumination in various ways. Recently, we reported on the implementation of a novel deep ultraviolet (DUV) frequencyquadrupled continuous wave (CW) light source emitting at λ = 193 nm in a mask-aligner and demonstrated test exposures [9].…”
Section: Introductionmentioning
confidence: 99%
“…Instead of a uniform illumination of the IFPs followed by blocking out most of the light and only redistributing the residual irradiance homogenously over the photomask, the team now reversed the setup order. An InnoLas Photonics' NANIO 355-3-V laser now replaces the conventional light source [2] and no illumination filter plates are needed anymore. Instead, a galvanometer scanner produces any desired angular spectrum for illuminating the photomask, always using the full laser power.…”
Section: Wwwiapuni-jenadementioning
confidence: 99%
“…Schematic overview of the new illumination system using the laser as an illumination source (a). A galvanometer scanner allows a flexible generation of angular spectra illuminating the photomask (b) [2]. …”
mentioning
confidence: 99%
“…In this study, gratings with an epoxy-based negative photoresist (SU-8) are fabricated by direct writing with a Ti:sapphire femtosecond laser at a wavelength of 800 nm, a pulse width of 67 fs, and a repetition rate of 80 MHz (Libra system, Coherent Inc.). Conventional techniques to fabricate diffraction gratings include photo-masking [21], electron beam lithography [22], etching techniques [23], and holographic interference [24,25]. Holographic lithography/recording was developed to create periodic 3D microstructures, in which periodic interference patterns such as an aspheric microlens structure [26], microscopic tubular structure [27], and fast bits [28], are printed into the photoresist by multi-laser beam irradiation.…”
Section: Introductionmentioning
confidence: 99%